In vivo study of bovine hydroxyapatite-gelatin-hydroxypropyl methylcellulose with alendronate as injectable bone substitute composite in osteoporotic animal model - Aniek Setiya Budiatin; Maria Apriliani Gani; Bulan Rhea Kaulika Hadinar Putri; Samirah Samirah; Dyah Hikmawati; Alfian Pramudita Putra; Nily Su'aidah; Junaidi Khotib (Wolters Kluwer Medknow Publications, 2022)
The injectable bone substitute (IBS) is a self-setting local drug delivery system that adjusts the shape of the bone gap in the fracture. This study aimed to examine the effectiveness of IBS composites of bovine hydroxyapatite (BHA) and alendronate (Ale) in accelerating bone growth in osteoporotic rats. IBS was made by mixing BHA with gelatin 5%, hydroxypropyl methylcellulose (HPMC) 2%, and Ale 10%. The physical properties of IBS were viscosity, injectability, and density tests. Twenty-four female Wistar rats were divided into four groups. After 8 weeks, 2 mm gap was made in the right femur of all rats and filled with IBS. The healing process was observed after 6 weeks with X-ray imaging and H and E staining. The obtained results showed viscosity, injectability, and density value of IBS from 30.4 to 39.4 dPa.s, 98.22%-98.64%, and 0.6325-0.8409 g/cm3, respectively. X-ray imaging and histology results proved the condition of osteoporosis in rats with ovariectomy. The addition of BHA-Gel-HPMC-Ale significantly affected the number of osteoblasts, osteocytes, and osteoclasts (P < 0.05). After 45 days of observation, the addition of BHA-Gel-HPMC-Ale showed the highest mean number of osteoblasts, osteocytes, and osteoclasts, which were 25.00 ± 3.00, 64.33 ± 11.15, and 5.67 ± 0.58 compared to BHA-Gel-HPMC and positive control groups. The BHA-Gel-HPMC-Ale IBS has the potential to reverse osteoporosis. Nevertheless, the underlying potential of these biomaterials to reverse osteoporosis needs further research.